Strategi Pengembangan Kompetensi Pustakawan Perpustakaan Perguruan Tinggi Negeri di Kota Pontianak - Sahidi Sahidi; Mifta Rahman; Atiqa Nur Latifa Hanum (Jurnal Pustaka Ilmiah, 2024)
This research aims to determine strategies for developing librarian competency as well as supporting and inhibiting factors for developing librarian competency in the Pontianak City State University Library. The method for exploring data in the field uses interviews and observations using the case study method with qualitative descriptive analysis. The informants used were the heads of libraries from the three universities and 2 librarians each in each college library. The results of the research show that the problems found in three State University libraries in Pontianak City include the low skills of librarians in using technology and the problem of educational qualifications of leaders who do not meet the standards for running university libraries in 2015 and 2017. Conclusions from the research show that the strategy is carried out through competency certification for equality as well as through training, workshops, national seminars in the field of librarians, becoming members of the IPI, and involving librarians in competitions for outstanding librarians. Efforts to improve librarian competence include leadership support and the availability of funds. Meanwhile, the inhibiting factor is a lack of awareness of increasing competence through education and support from the work environment.